From Divine Oracles to the Higher Criticism: Andrew D. White and the Warfare of Science with Theology in Christendom - Ungureanu, James C. (Zygon, 2021)
Historians of science and religion have given little attention to how historical-critical scholarship influenced perceptions of the relationship between science and religion in the nineteenth century. However, the so-called “cofounders” of the “conflict thesis,” the idea that science and religion are fundamentally and irrevocable at odds, were greatly affected by this literature. Indeed, in his two-volume magnum opus, A History of the Warfare of Science with Theology in Christendom (1896), Andrew D. White, in his longest and final chapter of his masterpiece, traced the development of the “scientific interpretation” of the Bible. In this article, I argue that developments in biblical criticism had a direct impact on how White constructed his historical understanding of the relationship between science and religion. By examining more carefully how biblical criticism played a significant role in the thought of White and other alleged cofounders of the conflict thesis, this article hopes to relocate the origins, development, and meaning of the science-religion debate at the end of the nineteenth century.